Which is the Best Screening Strategy for COPD among Smokers in Primary Care?. (2nd January 2017) - Llordés, Montserrat; Zurdo, Elba; Jaén, Ángeles; Vázquez, Inmaculada; Pastrana, Luís; Miravitlles, Marc
ABSTRACT: We developed a questionnaire to detect cases of chronic obstructive pulmonary disease (COPD) and compared its reliability with other strategies. In order to develop the new questionnaire (COPD screening questionnaire from Terrassa [EGARPOC]) we used data from an epidemiological study on the prevalence of COPD in smokers and calculated the odds ratio for each variable showing significance for the diagnosis of COPD on regression analysis. For comparison among questionnaires and the portable spirometer COPD-6, a cross-sectional multicenter study was performed. The study included 407 smokers or ex-smokers over the age of 40 years with no known diagnosis of COPD, who completed the different questionnaires (EGARPOC, Respiratory Health Screening Questionnaire, COPD-population screener and 2 questions) and underwent spirometry with the COPD-6. We determined the sensitivity, specificity, positive and negative predictive values (S, Sp, PPV and NPV, respectively) and the area under the receiver operating characteristic ROC curve (AUC ROC) of all the questionnaires and the different COPD-6 cut-offs. The prevalence of COPD was 26.3%. The EGARPOC questionnaire showed an S of 81.8%, an Sp of 70.6%, and an NPV of 91.8%; 73.3% of individuals were correctly classified, and the AUC ROC was 0.841. On comparing the questionnaires by the Chi-square test, the 2-question questionnaire showed the worst discrimination; while with an optimal cut-off of forced expiratory volume in one 1 second (FEV1 )/FEV6 of 0.78, the COPD-6 was significantly better than the questionnaires in the detection of COPD. Using a cut-off of FEV1 /FEV6 of 0.78 the COPD-6 was found to be the best screening tool for COPD in primary care compared to the questionnaires tested, which did not show differences among them.